Profitabilitas, Leverage, Kepemilikan Publik, dan Pengungkapan Corporate Social Responsibility - Pratiwi, Ni Putu Adelia Maya (E-Jurnal Akuntansi; Vol 33 No 7 (2023), 2023)
The aim of this study is to empirically examine the effect of profitability, leverage, and public ownership on the disclosure of corporate social responsibility (CSR) of SRI-KEHATI indexed companies. The causal relationship quantitative approach was carried out with secondary data sources originating from 85 sample company reports which were then analyzed through multiple linear regression. The research found that the results of leverage and public ownership have a positive effect on disclosure of corporate social responsibility, while profitability has a negative effect on disclosure of corporate social responsibility. The results of the research can contribute to the company's CSR disclosure policy by considering the factors that can influence CSR disclosure policies. Keywords: Corporate Social Responsibility Disclosure; Profitability; leverage; Public Ownership